Effect of psychopathic personality dimensions on counterproductive work behavior: a comparison model - Alia Azalea; Jun Wei Fong (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present study examined gender differences in the effects of psychopathic personality (i.e., attachment, behavioral, cognitive, dominance, emotional, and self) on counterproductive work behavior (CWB) (i.e., abuse, production deviance, sabotage, theft, and withdrawal) by analyzing their dimensions and components separately to gain a deeper understanding of the complexity of this relationship. Data were collected from 234 Malaysian employees using purposive sampling. Participants completed the Comprehensive Assessment of Psychopathic Personality Rating Form and Counterproductive Work Behavior Checklist. Data were analyzed using SPSS version 27 and a model was tested using Structural Equation Modelling through AMOS version 27. Gender differences were found in the effects of psychopathic personality dimensions – Attachment and Behavioral, on all counterproductive work behavior components and the effects of Cognitive, Dominance, Emotional, and Self dimensions on some counterproductive work behavior components. These findings suggest that the effect of psychopathic personality on counterproductive work behavior may yield different results for different psychopathic personality dimensions and counterproductive work behavior components in different genders and cultural contexts. The discussion includes considering psychopathic personality as a selection criterion during the employee selection process to minimize the occurrence of future counterproductive work behavior.